Pengaruh Risiko Dan Kualitas Layanan Terhadap Loyalitas Nasabah Pengguna BSI Mobile Banking - Sudirman, Muh Sajjaj; Imran, Muhammad; Prayoga, Dimas (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2024)
This study aims to see and examine the effect of risk and service quality on customer loyalty using BSI Mobile Banking for IAIN Ternate students. The source of data used in this study is primary data in the form of a questionnaire. This method uses a quantitative method, with a sample of 100 respondents from IAIN Ternate students who use BSI Mobile Banking, while the data collection technique used is a questionnaire method and processed using the SPSS program. From the results of data processing, it shows that the variables of Risk and Quality of Service all have a significant effect on the variable of customer loyalty in IAIN Ternate students